A Threshold-Limited Fluorescence Probe for Viscosity - Lei, Zuhai; Xin, Kai; Qiu, Shaobing; Hou, Liling; Meng, Xiangming; Yang, Youjun (Frontiers in Chemistry, 2019)
Viscosity of body fluid is an established biomarker of pathological conditions. Abnormality of cellular viscosity occurs when cells are challenged with external stresses. Small molecule probes to assess the viscosity are sought after for both disease diagnostics and basic studies. Fluorescence based probes are particular attractive due to their potentials for convenient and high spatiotemporal resolution microscopic monitoring of biological samples. The dyes with a floppy push-pull backbone or dyes with a rotatable substituent exhibits a viscosity responsive fluorescence enhancement and therefore viable viscosity probes. In the scaffold of the existing viscosity probes contains typically one such floppy site. Therefore, they typically linearly respond to log(viscosity). We argue that minor viscosity fluctuation could potentially be physiological as the biological system is dynamic. We wish to develop a conceptually new type, namely threshold-limited viscosity probes, to complement the existing probes. Such probes do not exhibit a fluorescence enhancement when challenged with minor and presumably physiological enhancement of viscosity. When the viscosity is higher than a certain threshold, their fluorescence turns on. We hypothesize that a dye with two far-apart floppy sites could potentially yield such a threshold-limited signal and designed VPZ2 and VPZ3. Through spectral titration, VPZ3 was found to yield the desired threshold-limited signal. VPZ3 was suitable for in vitro bioimging of viscosity under one-photon or two-photon excitation. VPZ3 is potentially a useful in many downstream applications. Future work includes fine-tune of the threshold to allow tailed limit for fluorescence turn-on to better meet the need of different applications. Besides the implications in the real-world applications, the design concept could also be translated to design of alternative substrates.